Determination issues of socio-economic welfare levels for standardly employed, precariat and unemployed persons (Journal of Economic Research & Business Administration, 2017)
Social welfare indicators of the population include the notion of wellbeingof the individual, groups and society as a whole. In the current crisisin Kazakhstan, the practice of using precarious labour contracts is increasingin order to implement the reduction in personnel costs strategy. It actualizesthe problem of the employment precarization’s impact on welfareof the majority of employees. Research is needed on distinguishing of theliving conditions for standardly employed, unemployed and precariat. Importantquestions arise about the indicators characterizing the pattern ofwell-being or ill-being for these groups of people, and the method, whichallows taking into account the multifactor in evaluating numerical valueof well-being. The new index of social progress enables each country toassess its position in the world, to identify the most painful points in implementationof social policy.